2014
DOI: 10.4103/0972-5229.128702
|View full text |Cite
|
Sign up to set email alerts
|

Snakebite profile from a medical college in rural setting in the hills of Himachal Pradesh, India

Abstract: Objective:The objective of the following study is to assess the clinical profiles and manifestations of snakebite patients in the rural hilly setting of Shivalik and the Lesser Himalayan region of Himachal Pradesh.Materials and Methods:A hospital record-based retrospective descriptive study was carried out that included details on demography, clinical profile, treatment and outcome among 200 patients over a period of 2 years. The data was analyzed using Chi-square test for comparison.Results:142 (71%) patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 15 publications
1
35
3
Order By: Relevance
“…[345678] P < 0.05 Our research shows that the Russell's viper is virtually nonexistent in North, and there is enough published evidence to prove this fact. [345678910111213141516] Neurotoxic snake Krait is responsible for high mortality throughout North India. [345678] Hence, the North Indian profile is neurotoxicity predominant (Krait), and South Indian profile is hemonephrotoxicity predominant (Russell's and saw-scaled vipers).…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…[345678] P < 0.05 Our research shows that the Russell's viper is virtually nonexistent in North, and there is enough published evidence to prove this fact. [345678910111213141516] Neurotoxic snake Krait is responsible for high mortality throughout North India. [345678] Hence, the North Indian profile is neurotoxicity predominant (Krait), and South Indian profile is hemonephrotoxicity predominant (Russell's and saw-scaled vipers).…”
Section: Introductionmentioning
confidence: 72%
“…North Indian snakes predominantly cause neurotoxicity in 70.95% of cases (877 envenomations) [Table 2]. [345678] P < 0.05 Our research shows that the Russell's viper is virtually nonexistent in North, and there is enough published evidence to prove this fact. [345678910111213141516] Neurotoxic snake Krait is responsible for high mortality throughout North India.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…In our ICU all patients received ASV and the mean ASV used for neuroparalytic snake bite was 22 vials which was nearer to the recommended dose of National snake bite management protocol 2008 (India). (13) Agarwal R and others observed that Low dose of snake antivenom is as effective as high dose in patients with severe neurotoxic snake envenomation. (14,15) As seen in our study, 66.66 % patients presented beyond 6 hours after the bite.…”
Section: Discussionmentioning
confidence: 99%
“…[1] We would like to share our experience and emphasize on the different management regimes being followed world over.…”
mentioning
confidence: 99%